Effect of redox potential on chalcopyrite dissolution imposed by addition of ferrous ions - Santos, Ana Laura Araújo [UNESP]; Arena, Fabiana Antonia [UNESP]; Benedetti, Assis Vicente [UNESP]; Bevilaqua, Denise [UNESP] (Ecletica Quimica, 2017)
Copper is one of the metals with great economic interest and about 70% of it is found in nature as chalcopyrite mineral (CuFeS2). Due to its slow dissolution kinetics, chalcopyrite dissolution is still a challenge for industries and researchers. Control of redox potential though has been said to be the key for increasing dissolution rate in chalcopyrite leaching systems. The current work investigated the effect of redox potential by ferrous ions addition on chalcopyrite (bio)leaching experiments. In abiotic systems, 90% of copper was leached into solution when redox potential was kept low (around 420 mV/Ag/AgCl) whereas in bacterial systems (610 mV/Ag/AgCl) low copper dissolution was observed. SEM analysis suggested presence of new phases that were confirmed by XRD to be elemental sulfur and jarosites and a significant decrease of chalcopyrite peak heights in these analyses was also observed. Jarosite was the only new phase detected in bacterial systems. Passivation of chalcopyrite surface did not occur in either conditions. The results clearly show that low redox potential along with presence of ferrous ions has positively influenced copper recovery, confirming the existence of a critical redox potential range where chalcopyrite dissolution is favored.
Keywords: Bioleaching; Chalcopyrite; Ferrous ions; Redox potential